Rating bacteriuria in children - Burstein de Herrera, Sonia (1968)
The urine of 500 children with various disease processes is studied. The samples were obtained directly, without using the catheter and the study of sediment, gram staining and quantitative culture was performed. Is proposed according to the distribution of bacterial counts , relating to the clinical picture and the study of sediment which significant bacteriuria horn to over 15,000 germs per ml is considered figures . According to this concept, of the 500 cases studied , 147 ( 29.4 %) were positive, with a greater incidence among newborns and infants s between school and pre - school . As for sex , between 0 and 2 years, the proportion of positivity was higher in men ; between 2 and 5 years , and was virtually unchanged between 5 and 12 years was higher in women. The most striking symptoms that prompted the request for examination , were fever , vomiting and diarrhea , which were more frequent in 0-2 years was more frequent cystitis from 2 to 12 years. The most commonly isolated bacteria were E. coli , 65.3 % : proteus , 35.37 % ; Klebsiella , Enterococcus 21.C8 % and 10.88 % . Mixed or several seeds crops is found in higher percentage in newborns and infants. The study revealed that sediment pyuria only found in 61.9 % of cases with significant bacteriuria. The sediment gram correlates in 96.6% of cases with counts of 1 x 10 bacteria . The quimioantibiograma showed that the most effective drugs " in vitro " against urinary germs are , nalidixic acid, nitrofurans , ampicillin, kanamycin and colistin .